2019
DOI: 10.1177/1075547019834566
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Communication Effectiveness, Communication Satisfaction, Self-Efficacy, and Self-Care Management Among Patients With Chronic Disease

Abstract: This study investigates channel choice and effective patient-provider communication, patient satisfaction, self-efficacy, and self-care management among patients with a chronic disease by applying and testing two prominent media choice theories: channel expansion theory and media synchronicity theory. A national sample of respondents with chronic disease completed measures assessing constructs from each theory. The model for media synchronicity theory provided a better fit for the data than did the model for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This also means that when there is no pre-existing physician–patient relationship, having a VC provides a new opportunity for establishing a relationship and communication structure. 49 Findings from a qualitative study support this idea, as it is found that knowing your physician before a VC was associated with higher VC satisfaction. 50 …”
Section: Factors Contributing To Vc Satisfactionmentioning
confidence: 86%
See 1 more Smart Citation
“…This also means that when there is no pre-existing physician–patient relationship, having a VC provides a new opportunity for establishing a relationship and communication structure. 49 Findings from a qualitative study support this idea, as it is found that knowing your physician before a VC was associated with higher VC satisfaction. 50 …”
Section: Factors Contributing To Vc Satisfactionmentioning
confidence: 86%
“…Channel expansion theory (CET) helps understand how the patient–physician relationship might impact VC satisfaction. 48 , 49 CET suggests that if a physician and patient have a pre-existing relationship that was established in person, having a VC may simply expand their existing communication and strengthen their relationship, leading to increasing VC satisfaction. This also means that when there is no pre-existing physician–patient relationship, having a VC provides a new opportunity for establishing a relationship and communication structure.…”
Section: Factors Contributing To Vc Satisfactionmentioning
confidence: 99%
“…However, future research should investigate how clinicians’ influence may be moderated by the mode of communication used to interact with at-risk relatives. For instance, synchronous communications between clinicians and at-risk relatives may strengthen fear and efficacy appeals as clinicians can more clearly express tone and benefit from the immediacy of those interactions compared to the less rich media formats of written communications [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyads who were not physically together during the interview may have interacted differently compared to dyads who were physically together. Dyads who were physically together during the interview may have had richer communication and more immediacy since they could see one another during the interview (Kashian & Mirzaei, 2019). Additionally, technical problems interrupted two interviews.…”
Section: Discussionmentioning
confidence: 99%